Case-Based Learning in Islamic Education: A Pedagogical Framework for Strengthening Student's Critical Thinking - Muhamad Basyrul Muvid (Maharot : Journal of Islamic Education, 2026)
Twenty-first-century learning requires instructional approaches that promote critical, innovative, and creative thinking through contextual and student-centered learning. However, Islamic Education remains largely dominated by conventional teaching practices that have not yet optimally fostered students’ critical thinking skills. This study aims to develop a conceptual and pedagogical framework for Case-Based Learning (CBL) in Islamic Education to strengthen students’ critical thinking skills. Using a library research approach, this study reviewed scholarly sources from Google Scholar, ERIC, academic books, reputable journal databases, and relevant scientific publications. The literature was analyzed through qualitative content analysis involving source selection, data reduction, categorization, comparison, interpretation, and conceptual synthesis. The analysis was guided by Constructivist Learning Theory, Experiential Learning Theory, Critical Thinking Theory, and the philosophical foundations of Islamic education associated with Al-Ghazali and Al-Attas. The synthesis indicates that CBL in Islamic Education can strengthen critical thinking by integrating cognitive, affective, and Islamic value dimensions through contextual real-life cases. The proposed framework guides students to identify problems, analyze causal factors, evaluate contextual situations, reflect on Islamic ethical principles, and formulate reasoned solutions systematically. These processes facilitate the development of higher-order thinking and critical thinking skills while strengthening students’ moral and religious awareness. The originality of this study lies in its integrative conceptual synthesis that connects CBL principles, twenty-first-century critical thinking competencies, and Islamic educational values within a coherent pedagogical framework. Unlike previous studies that have generally examined Case-Based Learning, critical thinking, or Islamic Education separately, this study provides a comprehensive framework that links contextual case analysis with Islamic ethical reflection and value-based decision-making. Thus, this study contributes theoretically and pedagogically to the development of contextual, student-centered, reflective, and value-based Islamic Education learning in the twenty-first century.